Improving care for patients with acute coronary syndromes: initial results from the National Audit of Myocardial Infarction Project (MINAP). Issue 9 (13th August 2004) - Birkhead, J S; Walker, L; Pearson, M; Weston, C; Cunningham, A D; Rickards, A F
Abstract : Objective: To describe the improvements in care that have followed the introduction of an electronic data entry and analysis system providing contemporary feedback on the management of acute coronary syndromes in 230 hospitals in England and Wales. Design: Observational study Methods: A secure electronic system was used to transfer encrypted data on patients with acute coronary syndromes from collaborating hospitals to central servers for analysis. Immediate online data entry to the central servers by hospitals allowed contemporary analyses of performance and immediate comparison with the national aggregate performance. Results: The records of 156 902 patients receiving a final diagnosis of acute coronary syndrome during three years between October 2000 and September 2003 were analysed. Of 69 113 patients with ST segment elevation infarction, 75.4% received thrombolytic treatment. Between the first and last years of the study the median interval from hospital arrival to treatment fell for eligible patients from 38 (interquartile range 22–58) to 20 (interquartile range 14–28) minutes. By mid 2003 77.6% were receiving thrombolytic treatment within 30 minutes of arrival. The proportion treated within two hours of onset of symptoms increased from 32.5% to 40.3% (a difference of 7.8 percentage points, p < 0.0001). The use of secondary prevention medication for acute coronary syndromes increased over this period: angiotensin converting enzyme inhibitors, 62.4% to 72.4%; β blockers, 76.3% to 82.6%; statins, 69.6% to 83.8%; and aspirin, 89.3% to 90.2%. Conclusion: The provision of contemporary online performance analyses has underpinned substantial improvement in the care of patients with acute coronary syndromes.